Improved hybrid inter and intra-cell interference cancellation mechanism for LTE-A HETNETS - S, Shibu; V, Saminadan (International Journal of Engineering and Technology, 2018)
In Heterogeneous networks (HetNets), operators need to ensure reliable service to their users in terms of network performance and low cost. The growing demand of user traffic necessitates the incorporation of femto cells and pico cells for facilitating seamless services. The network performance of Long Term Evolution (LTE) and LTE Advanced (LTE-A) HetNets is drastically influenced by the degree of interference that is realized in the inter-cell and intra-cell during communication. In this paper, an Improved Hybrid inter and intra-cell interference cancellation mechanism (CRS-IIC-LFLS) is propounded for handling interference at the inter and intra-cell level. Inter-cell interference cancellation is achieved through the use of an Improved CRS-IIC algorithm that uses the benefits of Linear Filtering Least Square (LFLS) method for channel estimation. CRS-IIC-LFLS is found to potent in rapid interference cancellation facilitation by suppressing the noise level, reducing the impact of fading channel and inherently eliminates small energy aware paths from large energy aware paths. The Simulation results confirm that the proposed scheme ensures better network throughput under light load, medium load and heavy load conditions of the network. The results prove that the performance of CRS-IIC-LFLS with CRS-IC-LFLS and CRS-IC-LLS based on spectral efficiency is improved at a mean rate of 21% and 26% respectively. The simulation results also portrays that the increase in the spectral efficiency of CRS-IIC-LFLS (64-QAM) is phenomenal to a maximum improvement of 12% over CRS-IIC-LFLS (16-QAM).Â Â